Nitric oxide synthase isoforms and NF-jB activity in normal and osteoarthritic human chondrocytes: Regulation by inducible nitric oxide - Rosa, Susana C. (2008)
To elucidate the role of endogenous inducible nitric oxide (NO) on the regulation of NF-jB activity in human chondrocytes, we evaluated (i) the pattern of expression of the neuronal (nNOS) and inducible (iNOS) NO synthase isoforms and the basal NF-jB activity in normal and osteoarthritic (OA) human chondrocytes, (ii) the role of cytokines and growth factors in modulating the protein levels of the two NOS isoforms, and (iii) the effect of inhibiting endogenous inducible NO production on the ability of interleukin- 1b (IL-1) to induce NF-jB activation. nNOS was more frequently expressed in normal than in OA chondrocytes, whereas the opposite was found for iNOS. IL-1 induced the degradation of both enzymes, but iNOS disappeared more rapidly. Although IjB-a was present in all the normal samples and in the majority of the OA samples, NF-jB–DNA binding activity in OA chondrocytes was increased approximately twofold relatively to normal cells. Addition of a NOS inhibitor, after induction of iNOS expression, induced IjB-a degradation and potenciated the effect of IL-1, indicating that endogenous inducible NO inhibits NF-jB activation. Taken together, these findings favor an inhibitory role of high NO levels on the regulation of NF-jB activation in chondrocytes, indicating that NF-jB activity is regulated, at least in part, by the balanced production of NO resulting from a dynamic process that, at any given moment, determines the availability of the constitutive and inducible NOS isoforms. Moreover, the down-regulatory role of NO on NF-jB activation warrants caution as to the possible utilization of NO inhibitors in the therapy of OA.